NEW GEOTECHNOLOGIES APPLIED TO THE GEOMORPHOLOGICAL STUDY: EXAMPLE OF MORPHOMETRY OF THE AREAL GULLY, CACEQUI-RS - Krein Rademann, Lucas (2020)
In the last decades the development of new technologies has brought about a great advance in science. In geotechnologies, one of the biggest advances was the development of Unmanned Aerial Vehicles that allow obtaining high quality data, with great potential for use in geomorphology. In this work, data obtained with aerial survey with UAV were used for the morphometric analysis of Voçoroca do Areal in Cacequi - RS. For this purpose, a flight was performed with a multirotor UAV, Phantom 4 at a flight height of 150m, afterwards the data were processed using the Structure from Motion algorithm. Afterwards, gully advance areas were classified and several morphometric parameters were calculated. The gully has different dynamics in different portions, having in the area upstream more extended and long areas of progress with smaller depths, in the central portion a large vertical development with a large eroded volume and in the downstream areas, with less intense advancement areas. Finally, the data obtained allowed the analysis of Voçoroca do Areal morphometry, providing data with extreme quality and accuracy. The use of these new geotechnologies still has a lot to contribute to the geomorphological analysis, mainly in the detailed mappings.